Combining Remote Sensing and Crop Models to Assess the Sustainability of Stakeholder‐Driven Groundwater Management in the US High Plains Aquifer. Issue 3 (5th March 2021) - Deines, Jillian M.; Kendall, Anthony D.; Butler, James J.; Basso, Bruno; Hyndman, David W.
Abstract: Nonrenewable groundwater contributes ∼20% of global irrigation water. As a result, key agricultural regions around the world are on unsustainable trajectories due to aquifer depletion, threatening food production and local economies. With increasing resource scarcity in the central High Plains Aquifer in the United States, an innovative stakeholder‐driven groundwater management framework emerged in Kansas referred to as the Local Enhanced Management Area (LEMA) program. This framework enables groups of irrigators to join together to implement measures to conserve groundwater. Here, we assessed the efficacy of the first LEMA to move the region toward sustainability with a process‐based crop model driven by well records and satellite‐derived annual land use. We found increased irrigation efficiency under the LEMA program reduced groundwater extraction by 25% (40 million m 3 ). However, only 22% of pumping reductions benefitted the net water balance (9 million m 3 ) due to decreased irrigation return flow resulting from increased irrigation efficiency. We then estimated economic impacts using simulated crop yields, commodity prices, and estimated energy saved from reduced groundwater pumping. Cost savings from reduced pumping were about 4.5 times greater than the income lost from minor yield penalties. This suggests that the program promotes both economic and water sustainability, but water targets may need to be more strict to stabilize groundwater levels. As aquifer depletion threatens crop production in many parts of the world, approaches that integrate dynamic process‐based models with in situ and satellite data can inform economically and hydrologically sustainable management strategies. Our work highlights the need to consider both economic factors and root zone processes when evaluating irrigation conservation programs. Key Points: We assessed management impacts with a satellite‐driven crop model, well data, commodity prices, and energy costs Groundwater reductions minimally decreased crop yields; improved irrigation efficiency limited the benefits to the aquifer water balance Energy cost savings exceeded yield penalties, increasing net profits while saving water